Diversity of scorpion fauna of Saswad-Jejuri, Pune District, Maharashtra, western India - S. Pande; D. Bastawade; A. Padhye; A. Pawashe (Journal of Threatened Taxa, 2012)
Our paper deals with the diversity of the scorpion fauna of Saswad-Jejuri region in western India, and highlights the conservation implications of quantitative studies. Eight species of scorpions from five genera and three families are recorded in 10 microhabitats. Some of these areas are categorized as âwastelandsâ and hence are vulnerable for land use modifications. The interdependence of such microhabitats and their neglected inhabitants like scorpions is highlighted in this study. This information provides a baseline biological data for further demographic and ecological studies and stresses the need for impact assessment prior to undertaking developmental projects in âwastelandsâ, since arachnids exhibit restricted movements and are vulnerable to habitat modification.